2007
DOI: 10.1093/eurheartj/ehm440
|View full text |Cite
|
Sign up to set email alerts
|

Reduced and delayed untwisting of the left ventricle in patients with hypertension and left ventricular hypertrophy: a study using two-dimensional speckle tracking imaging

Abstract: The observed delayed and reduced diastolic untwisting during the isovolumic relaxation period noted in hypertensive patients with LVH may contribute towards the LV relaxation abnormality. Two-dimensional speckle tracking imaging is a novel tool which can be used for the non-invasive assessment of LV relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
102
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 25 publications
15
102
2
3
Order By: Relevance
“…(2016) in healthy populations confirm data from clinical populations, where a decrease in cardiac mechanics is associated with an increase in LV after‐load (Takeuchi et al. 2007), which is an important finding when considering the continuum of hypertensive heart disease from raised after‐load to adverse LV remodeling to cardiac failure. It is conceivable that had Weiner et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) in healthy populations confirm data from clinical populations, where a decrease in cardiac mechanics is associated with an increase in LV after‐load (Takeuchi et al. 2007), which is an important finding when considering the continuum of hypertensive heart disease from raised after‐load to adverse LV remodeling to cardiac failure. It is conceivable that had Weiner et al.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of untwisting was significantly delayed in both systolic and diastolic HF. Takeuchi, et al 158 , demonstrated in hypertensive patients that while twist was similar among groups of patients with or without LVH, diastolic LV untwisting and untwisting rates were delayed and reduced in parallel to the severity of LVH. Of note, DD associated with normal aging does not cause a reduction in diastolic untwist as studies have shown normal twist mechanics in elderly individuals 159 , 160 .…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…[14][15][16] It has been shown that delayed and reduced diastolic untwisting during the diastolic phase may be an early indicator of an LV relaxation abnormality for hypertensive patients with LV hypertrophy. 17 Bansal et al 5 found that resting global LVrot and regional LVrot were significantly reduced in patients with myocardial infarction compared to those without previous myocardial infarction, and LVrot was most impaired in patients with multiple areas of infarction. Therefore, LVrot assessment represents an interesting approach for quantifying LV function and may provide important clinical information about cardiac function.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%